Prevention and Control of Seasonal Influenza with Vaccines: Recommendations of the Advisory Committee on Immunization Practices, United States, 2021–22 Influenza Season - Lisa A. Grohskopf; Elif Alyanak; Jill M. Ferdinands; Karen R. Broder; Lenee Blanton; H. Keipp Talbot; Alicia M. Fry (2021)
This report updates the 2020-21 recommendations of the Advisory Committee on Immunization Practices (ACIP) regarding the use of seasonal influenza vaccines in the United States (MMWR Recomm Rep 2020;69[No. RR-8]). Routine annual influenza vaccination is recommended for all persons aged ≥6 months who do not have contraindications. For each recipient, a licensed and age-appropriate vaccine should be used. ACIP makes no preferential recommendation for a specific vaccine when more than one licensed, recommended, and age-appropriate vaccine is available. During the 2021-22 influenza season, the following types of vaccines are expected to be available: inactivated influenza vaccines (IIV4s), recombinant influenza vaccine (RIV4), and live attenuated influenza vaccine (LAIV4).The 2021-22 influenza season is expected to coincide with continued circulation of SARS-CoV-2, the virus that causes COVID-19. Influenza vaccination of persons aged ≥6 months to reduce prevalence of illness caused by influenza will reduce symptoms that might be confused with those of COVID-19. Prevention of and reduction in the severity of influenza illness and reduction of outpatient visits, hospitalizations, and intensive care unit admissions through influenza vaccination also could alleviate stress on the U.S. health care system. Guidance for vaccine planning during the pandemic is available at https://www.cdc.gov/vaccines/pandemic-guidance/index.html. Recommendations for the use of COVID-19 vaccines are available at https://www.cdc.gov/vaccines/hcp/acip-recs/vacc-specific/covid-19.html, and additional clinical guidance is available at https://www.cdc.gov/vaccines/covid-19/clinical-considerations/covid-19-vaccines-us.html.Updates described in this report reflect discussions during public meetings of ACIP that were held on October 28, 2020; February 25, 2021; and June 24, 2021. Primary updates to this report include the following six items. First, all seasonal influenza vaccines available in the United States for the 2021-22 season are expected to be quadrivalent. Second, the composition of 2021-22 U.S. influenza vaccines includes updates to the influenza A(H1N1)pdm09 and influenza A(H3N2) components. U.S.-licensed influenza vaccines will contain hemagglutinin derived from an influenza A/Victoria/2570/2019 (H1N1)pdm09-like virus (for egg-based vaccines) or an influenza A/Wisconsin/588/2019 (H1N1)pdm09-like virus (for cell culture-based and recombinant vaccines), an influenza A/Cambodia/e0826360/2020 (H3N2)-like virus, an influenza B/Washington/02/2019 (Victoria lineage)-like virus, and an influenza B/Phuket/3073/2013 (Yamagata lineage)-like virus. Third, the approved age indication for the cell culture-based inactivated influenza vaccine, Flucelvax Quadrivalent (ccIIV4), has been expanded from ages ≥4 years to ages ≥2 years. Fourth, discussion of administration of influenza vaccines with other vaccines includes considerations for coadministration of influenza vaccines and COVID-19 vaccines. Providers should also consult current ACIP COVID-19 vaccine recommendations and CDC guidance concerning coadministration of these vaccines with influenza vaccines. Vaccines that are given at the same time should be administered in separate anatomic sites. Fifth, guidance concerning timing of influenza vaccination now states that vaccination soon after vaccine becomes available can be considered for pregnant women in the third trimester. As previously recommended, children who need 2 doses (children aged 6 months through 8 years who have never received influenza vaccine or who have not previously received a lifetime total of ≥2 doses) should receive their first dose as soon as possible after vaccine becomes available to allow the second dose (which must be administered ≥4 weeks later) to be received by the end of October. For nonpregnant adults, vaccination in July and August should be avoided unless there is concern that later vaccination might not be possible. Sixth, contraindications and precautions to the use of ccIIV4 and RIV4 have been modified, specifically with regard to persons with a history of severe allergic reaction (e.g., anaphylaxis) to an influenza vaccine. A history of a severe allergic reaction to a previous dose of any egg-based IIV, LAIV, or RIV of any valency is a precaution to use of ccIIV4. A history of a severe allergic reaction to a previous dose of any egg-based IIV, ccIIV, or LAIV of any valency is a precaution to use of RIV4. Use of ccIIV4 and RIV4 in such instances should occur in an inpatient or outpatient medical setting under supervision of a provider who can recognize and manage a severe allergic reaction; providers can also consider consulting with an allergist to help identify the vaccine component responsible for the reaction. For ccIIV4, history of a severe allergic reaction (e.g., anaphylaxis) to any ccIIV of any valency or any component of ccIIV4 is a contraindication to future use of ccIIV4. For RIV4, history of a severe allergic reaction (e.g., anaphylaxis) to any RIV of any valency or any component of RIV4 is a contraindication to future use of RIV4. This report focuses on recommendations for the use of vaccines for the prevention and control of seasonal influenza during the 2021-22 influenza season in the United States. A brief summary of the recommendations and a link to the most recent Background Document containing additional information are available at https://www.cdc.gov/vaccines/hcp/acip-recs/vacc-specific/flu.html. These recommendations apply to U.S.-licensed influenza vaccines used according to Food and Drug Administration-licensed indications. Updates and other information are available from CDC's influenza website (https://www.cdc.gov/flu); vaccination and health care providers should check this site periodically for additional information.